Cell Surface Differentiation Antigens of the Malignant T Cell in Sezary Syndrome and Mycosis Fungoides - Haynes, Barton F. (1981)
Using a panel of monoclonal antibodies and rabbit heteroantisera, we have studied the cell surface markers of peripheral blood (PB) Sezary cells from six patients with mycosis fungoides or Sezary syndrome, disease grouped within the spectrum of cutaneous T cell lymphomas (CTCL). Furthermore, we have studied two cell lines (Hut 78 and Hut 102) derived from malignant Sezary T cells from CTCL patients. The monoclonal antibody 3A1 defines a major human PB T cell subset (85% of PB T cells) while the antigen defined by the monoclonal antibody 4F2 is present on a subset (70%) of activated PB T cells and on circulating PB monocytes. In contrast to normal subjects in whom 60-70% of circulating PB mononuclear cells were 3A1(+) T cells, PB mononuclear cells from six CTCL patients studied had an average of only 10.6±3.2% 3A1(+) T cells. Whereas 85% of E-rosette positive cells from normal individuals were 3A1(+), virtually all E-rosette positive T cells from the Sezary patients were 3A1(-). Two patients with high numbers of circulating Sezary T cells had both aneuploid and diploid PB T cell populations present; after separation of PB T cells into 3A1(+) and 3A1(-) cell suspensions, all 3A1(-) cells were found to be aneuploid. In contrast to normal resting PB T cells which were 4F2(-), all PB Sezary cells were 4F2(+), suggesting a state of activation. The 3A1 antigen was on a variety of acute lymphoblastic leukemia T cell lines (HSB-2, RPMI-8402, MOLT4, CEM) but was absent on the Hut 78 and Hut 102 Sezary T cell lines. Using rabbit anti-human T and anti-human Ia (p23, 30) antisera, we found that all malignant Sezary PB cells tested were killed by anti-T cell antiserum plus complement but not by anti-Ia plus complement. In contrast, Sezary cell lines Hut 78 and 102, were killed by both anti-T cell antiserum and anti-Ia plus complement. Similar to 3A1(-) normal PB T cells, 3A1(-) Sezary PB T cells proliferated poorly to phytohemagglutinin and concanavalin A. However, 3A1(-) Sezary T cells were able to provide T cell help towards pokeweed mitogen-induced in vitro B cell immunoglobulin synthesis, an immunoregulatory function limited to 3A1(+) T cells in normal subjects. Thus, the 3A1 antigen is present on 85% of normal PB T cells, and on most T-acute lymphoblastic leukemia lines tested; in contrast the 3A1 antigen is not present on the majority of circulating malignant Sezary PB T cells nor on T cell lines derived from malignant Sezary T cells. The lack of expression of the 3A1 antigen may be associated with malignant transformation of T cells in CTCL and may be an important marker for tracing the clonal origin of the malignant Sezary T cell.